2020
DOI: 10.3390/ijerph17051689
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescents’ Reactions to Adverts for Fast-Food and Confectionery Brands That are High in Fat, Salt, and/or Sugar (HFSS), and Possible Implications for Future Research and Regulation: Findings from a Cross-Sectional Survey of 11–19 Year Olds in the United Kingdom

Abstract: The influence that marketing for foods high in fat, salt, and/or sugar (HFSS) has on adolescents extends beyond a dose-response relationship between exposure and consumption. It is also important to explore how marketing shapes or reinforces product/brand attitudes, and whether this varies by demography and Body Mass Index (BMI). To examine this, a cross-sectional survey was conducted with 11–19 year olds in the United Kingdom (n = 3348). Participants watched 30 s video adverts for a fast-food and confectioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…There is evidence that preschool children exposed to adverts for a range of child-directed foods had positive attitudes about these foods, 83 and that adolescents reported positive attitudes after viewing online adverts for fast food and confectionery. 84 Comparing digital and nondigital advertising formats, we found no difference in impact on attitudes in subgroup meta-analysis, but narrative synthesis indicated that understanding was lower for digital formats. This is unsurprising since digital advertising is more integrated and, therefore, may be less explicit and more difficult to identify and understand, in addition to greater personalization and targeting.…”
Section: Discussionmentioning
confidence: 72%
“…There is evidence that preschool children exposed to adverts for a range of child-directed foods had positive attitudes about these foods, 83 and that adolescents reported positive attitudes after viewing online adverts for fast food and confectionery. 84 Comparing digital and nondigital advertising formats, we found no difference in impact on attitudes in subgroup meta-analysis, but narrative synthesis indicated that understanding was lower for digital formats. This is unsurprising since digital advertising is more integrated and, therefore, may be less explicit and more difficult to identify and understand, in addition to greater personalization and targeting.…”
Section: Discussionmentioning
confidence: 72%
“…Younger teens respond more to the presence of positive reactions to advertising, such as attractiveness to the look, and the temptation to try, but are hindered by the health perception of high-sugar products. The younger group has the ability to recognize the commercial intent and persuasive marketing is not very developed (20).…”
Section: Discussionmentioning
confidence: 99%
“…20,21,96 Online survey studies with adolescents in Australia and the United Kingdom have correlated digital media use (self-reported media or platform use, and brands engaged with), or responses to food ads, with self-reported eating. 91,92 Finally, although the body of studies assessing food company websites and advergames was not included in this review, we note that a meta-analysis of food marketing advergames concludes that encountering embedded branding or advertising within content such as games influences children's subsequent food consumption. 97 Furthermore, where data indicate that children frequently access food company websites and/or advergames, we recommend that studies are conducted to measure likely exposure and power (accordingly, the protocols described in Section 4 provide appropriate guidance).…”
Section: Impact Of Digital Marketing On Attitudes and Behaviorsmentioning
confidence: 99%